Synthesis, Characterization and Invivo Evaluation of Poly Sulfoxy Amine Grafted Xanthan Gum: Pharmaceutical Science-Chemistry for New drug discovery - Rahul Laxman Jadhav; Manisha Vyankatrao Patil; Shaikh Siraj N (International Journal of Life Science and Pharma Research, 2022)
Natural polymers are hydrophilic in nature, economic, chemically inert, easily available, biodegradable, and non-toxic. Following problems associated with the use of gums include uncontrolled rates of hydration, pH dependent solubility, thickening, drop in viscosity on storage, and the possibility of microbial contamination. Chemical modification of gums not only minimizes these drawbacks but also alter their physicochemical properties. Recently, researchers have been modifying properties of natural gums to explore its more applicability. Aim of the current study was to explore Xanthan gum’s applicability in mucoadhesive and other property by doing its Chemical modification. Sulfoxy amine modification of xanthan gum was carried out by reacting xanthan gum with thionyl chloride and further treated with ammonia. FTIR, elemental DSC, XRD and SEM were studied for confirmation of the modification. The modified xanthan gum showed improvement in the mucoadhesion, water uptake capacity, gelling property as well as viscosity as compared to unmodified xanthan gum. The results of X-ray diffraction study confirms the finding of DSC study. X-ray diffractogram confirmed XG is typical of amorphous substance while that of MXG is typical of crystalline substance with the characteristic peak appearing at 14.79, 25.66, 29.63 and 31.82 2θ. The 0.6% w/v of modified xanthan gum showed gelling property. The 0.6% w/v of modified Xanthan Gum showed gelling property where as Xanthan Gum required more than 1% w/v , it indicate that gelling property of Xanthan Gum has improved due to its modification. Mucoadhesive strength of modified xanthan gum was found to be 4±0.56 gm which is more than xanthan gum i.e. 1.5±0.94 gm. The ionic interactions may be taken place in between negatively charged mucus with cationic modified polymer and superior mucoadhesion can be achieved. Rapid and constant swelling behavior was observed by modified Xanthan gum. The SEM image of MXG showed that the grafting of Polysulfoxyamine onto XG brings about the change in the shape and size of the XG particles. The enhanced viscosity and gelling capacity of modified xanthan gum were also observed as compared to xanthan gum. In vivo acute toxicity study of Poly sulfoxy amine grafted xanthan gum was performed. The toxicological effects were observed in terms of mortality and expressed as LD50. Results of Acute toxicity study shows LD50 value was more than 2 gm/kg indicating the low toxicity. These findings proved that modified xanthan gum may be used as promising excipient in various drug delivery systems.